A Prospective Study of Pattern of Custodial Deaths of Autopsies Conducted at SMS Hospital Jaipur During 2017-18 (Medico Legal Update, 2019)
Deaths occurring in police custody incite enormous amount of emotions from relatives of deceased andspeculations from media and general public. A person in custody is entirely dependent on his custodiansfor his basic requirements; hence this type of death raises questions regarding living conditions, inhumanetreatment and violation of fundamental rights of prisoners.This prospective observational study was carried out during period April 2017 to March 2018 in Departmentof Forensic Medicine, at SMS Medical College, Jaipur, Rajasthan. 20 cases of alleged Deaths in custodyduring study period were observed on the subjects of socio-demographic profile of deceased, circumstancesprior to deaths, treatment taken, postmortem findings and cause of deaths. The data so obtained wasstatistically analysed. This study observed that maximum cases were male (95%); age group above 61years (30%); urban domicile (65%). Maximum cases were brought in month of February (25%) followedby January (20%). Most prisoners died in hospital during treatment (80%). Natural causes of death werecommoner than unnatural causes. Histopathological observations were most common for carcinoma (25%)followed by myocardial infarction (20%).